Analisis Pengelolaan Distribusi Bahan Baku dari Supplier Untuk UMKM Coffee Shop - Yogi Nadianto (Jurnal Indonesia Sosial Teknologi, 2022)
MANDIKA TEKNIK MAKMUR is a company engaged in the sale of coffee since 2010 which is located at Jl. Ruko Roxy Blok RB No. 7, Jalan Villa Mutiara 1, South Cikarang, Ciantra, Cikarang Sel, Bekasi, West Java, in the process of ordering by the customer or recording coffee orders still using stationery manually which is considered to be less efficient in terms of time I think it's not neat in filing order data. These problems are deemed inefficient in terms of marketing and managing orders in the current digital era, therefore we need an online marketing and management media or website that can be accessed en masse to facilitate UD. MANDIKA TEKNIK MAKMUR in selling and introducing the profile and quality of service, for coffee shop customers who will order their coffee, making it easier to choose prices according to the budgeted costs from their coffee stock providers that have been provided by UD. MANDIKA TEKNIK MAKMUR and published through the website so that they can manage customer relations. The number of coffee shops who complain about the stock of goods that do not match and so that sales cannot run optimally, Many coffee stock items are not recorded properly so they experience a lot of losses due to unorganized recording, and people complain that they cannot meet the needs of their coffee shop because when they are going to suddenly buying goods are not available, because the management system from suppliers is less efficient and still conventional.